REPURCHASE INTENTION DITINJAU DARI BRAND IMAGE, BRAND TRUST DAN LIFESTYLE (STUDI KASUS PADA PRODUK NEVADA DI SURAKARTA) - Aloysia Syafa Kusumasari (Jurnal Ekonomi dan Bisnis, 2020)
ABSTRACTThe purpose of this  study  was  to  determine the  effect of brand image, brand trust, and lifestyle  on repurchase intention of Nevada  products  in  Surakarta.  This  type  of  research  uses  quantitative descriptive research. The population in this study were all consumers who had bought Nevada products more than twice. The sample of the study was 100 responden using purposive sampling technique. Methods  of data  using  a  questionnaire.  The  data  analysis  technique  used  in this study was multiple linear regression analysis  technique.  The conclusion  of6this  study  is  that brand image has  a significant  effect  on repurchase  intention, brand trust  and lifestyle have   no significant effect on repurchase intention.